2016
DOI: 10.1016/j.jamda.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of High-Protein Oral Nutritional Supplements Among Malnourished Men and Women with Sarcopenia: A Multicenter, Randomized, Double-Blinded, Controlled Trial

Abstract: ONS improved strength outcomes in malnourished older adults with sarcopenia. In those with mild-moderate sarcopenia, but not severe sarcopenia, consumption of the E improved leg muscle strength and quality compared with the standard C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 54 publications
2
136
1
4
Order By: Relevance
“…HMB has been shown to act as a potent stimulator of protein synthesis as well as an inhibitor of protein breakdown. 38 A growing body of evidence suggests that HMB or oral nutrition supplements containing HMB may help to slow or even reverse muscle loss in aging, illness, or starvation 39,40 and improve other important outcomes such as wound healing, 41 physical function, 42 and mortality. 43 Therefore, using a high-protein ONS or enteral tube feeding that contains HMB may help in the management of malnutrition and muscle mass loss.…”
Section: Identify and Assess Low Muscle Mass For Those At Risk Of Malmentioning
confidence: 99%
“…HMB has been shown to act as a potent stimulator of protein synthesis as well as an inhibitor of protein breakdown. 38 A growing body of evidence suggests that HMB or oral nutrition supplements containing HMB may help to slow or even reverse muscle loss in aging, illness, or starvation 39,40 and improve other important outcomes such as wound healing, 41 physical function, 42 and mortality. 43 Therefore, using a high-protein ONS or enteral tube feeding that contains HMB may help in the management of malnutrition and muscle mass loss.…”
Section: Identify and Assess Low Muscle Mass For Those At Risk Of Malmentioning
confidence: 99%
“…Table shows the main characteristics of included studies. Of the included studies, 16 studies had a two‐arm randomised controlled trial (RCT) design (Andersson, Hulander, Rothenberg, & Iversen, ; Beelen et al, ; Cramer et al, ; Deutz et al, ; Ekinci et al, ; Fernández‐Barrés et al, ; Gariballa, Forster, Walters, & Powers, ; Kim & Lee, ; Luger, Dorner, et al, ; Munk et al, ; Myint et al, ; Neelemaat, Bosmans, Thijs, Seidell, & van Bokhorst‐de van der Schueren, ; Rondanelli et al, ; Sharma et al, ; Stange et al, ; Veronese et al, ). One study had a two‐arm cluster RCT design (Salvà et al, ), and three studies had a three‐arm RCT design (Botella‐Carretero et al, ; Hin et al, ; Pedersen, Pedersen, & Damsgaard, ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were considered to have a low risk of bias (Hin et al, ; Luger, Dorner, et al, ; Neelemaat et al, ), whereas four studies showed some concerns (Andersson et al, ; Deutz et al, ; Gariballa et al, ; Kim & Lee, ), and 14 studies were assessed to be at high risk of bias (Beelen et al, ; Botella‐Carretero et al, ; Cramer et al, ; Ekinci et al, ; Fernández‐Barrés et al, ; Munk et al, ; Myint et al, ; Pedersen et al, ; Rondanelli et al, ; Salvà et al, ; Sharma et al, ; Stange et al, ; Veronese et al, ; Ziylan et al, ; Table ). Main threats for the methodological quality were as follows: (a) blinding of participants, caregivers, assessors and/or research data analysts was either not performed in the study or reported in the article; (b) lack of reporting significance of differences in baseline characteristics between intervention and control group; (c) incomplete data for all outcomes and absence of intention‐to‐treat analysis; and (d) lack of transparency in complete reporting due to absence of detailed information from previously published study protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [35] demonstrated that improvements in clinically relevant measures, such as strength and functionality, could be achieved by supplementation with high-quality oral nutritional supplementation.…”
Section: Nutritional Interventions To Prevent Sarcopeniamentioning
confidence: 99%